p-CuO/n-Si heterojunction solar cells with high open circuit voltage and photocurrent through interfacial engineering - Masudy-Panah, S.; Dalapati, G.; Radhakrishnan, K.; Kumar, A.; Tan, H.; Elumalai, Naveen Kumar; Vijila, C.; Tan, C.; Chi, D. (2015)
Heterojunction solar cells of p‐type cupric oxide (CuO) and n‐type silicon (Si), p‐CuO/n‐Si, have been fabricated using conventional sputter and rapid thermal annealing techniques. Photovoltaic properties with an open‐circuit voltage (Voc) of 380 mV, short circuit current (Jsc) of 1.2 mA/cm2, and a photocurrent of 2.9 mA/cm2 were observed for the solar cell annealed at 300 °C for 1 min. When the annealing duration was increased, the photocurrent increased, but the Voc was found to reduce because of the degradation of interface quality. An improvement in the Voc resulting to a record value of 509 mV and Jsc of 4 mA/cm2 with a high photocurrent of ~12 mA/cm2 was achieved through interface engineering and controlling the phase transformation of CuO film. X‐ray diffraction, X‐ray photoelectron spectroscopy, and high‐resolution transmission electron microscopy analysis have been used to investigate the interface properties and crystal quality of sputter‐deposited CuO thin film. The improvement in Voc is mainly due to the enhancement of crystal quality of CuO thin film and interface properties between p‐CuO and n‐Si substrate. The enhancement of photocurrent is found to be due to the reduction of carrier recombination rate as revealed by transient photovoltage spectroscopy analysis.